Coxiella burnetii Seroprevalence and Risk Factors in Cattle Farmers and Farm Residents in Three Northeastern Provinces and Inner Mongolia Autonomous Region, China - Sun, Wu-Wen (Biomed Res Int, 2016)
Little is known about Coxiella burnetii infection among cattle farmers and farm residents in China. Thus, the present study was conducted to detect the seroprevalence of C. burnetii infection and estimate associated risk factors among cattle farmers and farm residents in China. A cross-sectional study was designed, and sera of 362 people living or working on 106 cattle farms were tested for C. burnetii IgG and IgM antibodies by immunofluorescence assay. Overall C. burnetii seroprevalence was 35.6% (129/362, 95% CI: 30.70–40.57), and 112 participants had experienced a past infection and seventeen (4.7%) had experienced a relatively recent infection. In the final combined multilevel model, the following activities were significantly associated with presence of antibodies against C. burnetii: milking cattle, providing general healthcare to cattle, providing birth assistance, contact dead-born animals, urbanization, and presence of mice and/or rats in the stable. Moreover, presence of disinfection equipment was a significant protective factor. This is the first study addressing the seroprevalence and risk factors of C. burnetii infection in cattle farmers and farm residents in three northeastern provinces and Inner Mongolia Autonomous Region, China.